IMPROVING THE TOOLS OF THE STATE ADMINISTRATION OF LOCAL ECONOMIC DEVELOPMENT IN UKRAINE - PRIAMUKHINA, Natalia; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study revealed the relevance of the problem of improving the system of tools that can be effectively used to ensure effective and balanced, problem-oriented local socio-economic development of the territories of Ukraine. The purpose of the research is to carry out analysis and identification of problematic aspects, as well as to justify recommendations in terms of improving the tools of local economic development management on the example of one of the territorial communities of Ukraine. On the example of one of the territorial communities of Ukraine, the economic activity of economic entities operating on its territory is analyzed, in particular, the structure of the types of economic activity of the territorial community is shown, the structure of employment of the population of the territorial community by types of economic activity is reflected, the indicators of employment, wages and income are characterized of the local budget by spheres of management of the territorial community. On this basis, the key obstacles to local economic development were determined, in particular, the high level of subsidies, dependence on higher-level budgets, as well as the functioning of public and communal sector organizations in the community; low level of development of business entities that represent the real sector of the economy or basic types of economic activity; weak business and business activity of the local population; its focus on interregional and intraregional labor migration; insufficient investment attractiveness of the territory for the accumulation of investment resources for the creation of new industries, including branches of processing industry; limited practices of vertical-horizontal integration of business entities, creation of cluster structures, integration with business entities from neighboring communities and the regional center; the underdevelopment of the elements of the system of preservation, formation and expansion of the intellectual and personnel resource for the activation of local economic and social development. It has been proven that in order to overcome these obstacles to local economic development, an arsenal of state management tools such as financial and investment (creation of industrial parks, growth centers, clusters; public-private partnership; financial leasing and outsourcing; crowdfunding; creation of revolving funds) should be formed and gradually implemented ), budgetary (tax incentives; implementation of local social and economic programs; inter-municipal cooperation; use of participatory budgets), credit (attraction of bank and other lending; provision of guarantees; creation of financial support funds; local bond loans), grant (attraction of resources of international technical, including financial, aid; formation and implementation of grant programs and projects) and socio-economic ( stimulation of employment, self-employment, development of entrepreneurship, including social entrepreneurship; provision of social housing; implementation of social inclusion projects).